Economic diversification strategies : a key driver in Africa's new industrial revolution - Asche, Helmut (UNIDO ViennaAT, 2012)
Recommends that African countries strive for diversification in higher-valued products and later specialise in more highly sophisticated items. States that if Africa deliberately aims at diversification, new industrial policies are needed to support the exploitation of industrial potentials.